Pesticide dichorvos induces early solid Ehrlich tumoral development associated with a non-protective pro-inflammatory response - de Camargo, Marcela Rodrigues [UNESP]; Akamine, Pedro Vinicius Teruya [UNESP]; Venturini, James [UNESP]; de Arruda, Maria Sueli P. [UNESP]; da Silva Franchi, Carla Adriene [UNESP] (Springer Nature, 2018)
Prolonged exposure to dichlorvos (DDVP), a common pesticide used for food crops, has been related to the development of infections and malignancies. Macrophages are used as bioindicators of immunotoxicity; thus, evaluation of their activity in solid Ehrlich tumor-bearing mice (TBM) may be useful to evaluate the influence of pesticides on human health. To investigate the effects of low DDVP doses, Swiss mice were divided into the following groups: the DDVP group, composed of mice fed diets containing 10 mg/kg of DDVP; the TBM group, consisting of mice subcutaneously inoculated with 107 tumor cells/100 μl and fed a basal diet; the DDVP-TBM group, consisting of mice previously fed DDVP-containing diets for 28 days and then subcutaneously inoculated with tumor cells; and the control (CTRL) group, composed of mice fed a basal diet. After 7 and 21 days of tumor inoculation, the mice were euthanized; and after necroscopic examination, the neoplastic mass, organs, and intraperitoneal fluid were collected. Adherent peritoneal cells were cultivated to determine the production of H2O2 and TNF. Altogether, our results indicate that even at low doses, the intake of DDVP caused weight loss and increased tumor mass, which were associated with H2O2 production and high levels of TNF, a pro-inflammatory cytokine. These data are important as the exposure to pesticides, even at low doses, could potentially hinder the immune response against tumors and, consequently, create favorable conditions for their development.
Keywords: Cytokines; Dichorvos; Ehrlich tumor; Immunotoxicity; Macrophage activity; Organophosphorus